Relationships between performance and the run-up speed, phase distances and ratios in the female triple jump - Shibata, A.; Shimizu, Y.; Koyama, H. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
The aim of this study was to clarify the relationships between performance in the female triple jump and the run-up speed, phase distances and ratios, in order to propose basic target values corresponding to performance level. The subjects were 100 female triple jumpers (official record: 15.20-11.23 m) who participated in the World Championships (WC) and competitions held in Japan. They were divided into 5 groups based on the effective jumping distance (15G: = 15.00 m, 14G: 14.00-14.99 m, 13G: 13.00-13.99 m, 12G: 12.00-12.99 m, 11G: = 11.99 m). The run-up speed and phase distances in the WC were collected with reference to previous reports of the WC trials, and those of the Japanese competitions trials were measured using a laser distance measurement device (LAVEG) and a high-speed camera. The result of correlation analysis revealed that significant positive correlations were found between performance and the maximal run-up speed (r=0.878) and phase distances (r=0.826-0.907). However, phase ratios were not correlated with performance (r=-0.110-0.082). Comparison of the 5 groups revealed that 15G, which represents world elite level, developed performance by significantly extending the jump distance, although the hop and step distances were not different from those of 14G. In 13G representing Japanese elite level, performance was developed by significantly extending the hop and step distances relative to 12G, and the step distance in 13G was as long as that in 14G. On the other hand, the hop and jump distances in 13G were not as long as those in 14G. These results suggest that the run-up speed and phase distances are important factors for development of performance, although the strategy for acquiring the jumping distance in each phase differs with performance level.